Inhibition of Nociception in a Preclinical Episodic Migraine Model by Dietary Supplementation of Grape Seed Extract Involves Activation of Endocannabinoid Receptors - Woodman, Sara E.; Antonopoulos, Sophia R.; Durham, Paul L. (Frontiers in Pain Research, 2022)
Migraine is associated with peripheral and central sensitization of the trigeminal system and dysfunction of descending pain modulation pathways. Recently, dietary inclusion of grape seed extract (GSE) was shown to inhibit mechanical nociception in a preclinical model of chronic temporomandibular joint disorder, a condition often comorbid with migraine, with the antinociceptive effect mediated, in part, by activation of 5-HT3/7 and GABAB receptors. This study further investigated the mechanisms by which GSE inhibits mechanical nociception in a preclinical model of episodic migraine. Hyperalgesic priming of female and male Sprague Dawley rats was induced by three consecutive daily two-hour episodes of restraint stress. Seven days after the final restraint stress, rats were exposed to pungent odors from an oil extract that contains the compound umbellulone, which stimulates CGRP release and induces migraine-like pain. Some animals received dietary supplementation of GSE in their drinking water beginning one week prior to restraint stress. Changes in mechanical sensitivity in the orofacial region and hindpaw were determined using von Frey filaments. To investigate the role of the endocannabinoid receptors in the effect of GSE, some animals were injected intracisternally with the CB1 antagonist AM 251 or the CB2 antagonist AM 630 prior to odor inhalation. Changes in CGRP expression in the spinal trigeminal nucleus (STN) in response to stress, odor and GSE supplementation were studied using immunohistochemistry. Exposure of stress-primed animals to the odor caused a significant increase in the average number of withdrawal responses to mechanical stimulation in both the orofacial region and hindpaw, and the effect was significantly suppressed by daily supplementation with GSE. The anti-nociceptive effect of GSE was inhibited by intracisternal administration of antagonists of CB1 and CB2 receptors. GSE supplementation inhibited odor-mediated stimulation of CGRP expression in the STN in sensitized animals. These results demonstrate that GSE supplementation inhibits trigeminal pain signaling in an injury-free model of migraine-like pain via activation of endocannabinoid receptors and repression of CGRP expression centrally. Hence, we propose that GSE may be beneficial as a complementary migraine therapeutic.